Clinical characteristics and infectivity of asymptomatic carriers of SARS-CoV-2 (Review) - Zhang, Wanying (Exp Ther Med, 2021)
Since December 2019, the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic. At present, confirmed patients are the main source of infection, while a number of studies have indicated that asymptomatic carriers also have the ability to spread the virus. As of September 29, 2020, as the first country to report coronavirus disease 2019 (COVID-19), China has 375 asymptomatic infections according to the National Health Commission of China. Asymptomatic carriers have become the current focus of global epidemic prevention and control efforts. The present review article provides a brief introduction on the clinical characteristics and infectivity of asymptomatic carriers, and makes suggestions for the identification of asymptomatic carriers.